(untitled) (Journal of the College of Education for Women, 2019)
The present theoretical study concerning the relation between anthropology and education has discovered the existence of differences in points of view between teachers related to socialization. Anthropologists see socialization as the process in the child acquires the culture of society tike shills, habits, types of behaviors, norms and social values. Sociologists concentrate on the problems of learning, and the types of social behaviors. Social sciences can be considered as integrated unity concerning the realization of objectives. However they hold various opinions about this subject.